Effect of mechanical tension on fibroblast transcriptome profile and regulatory mechanisms of myocardial collagen turnover. Issue 4 (1st March 2023) - Shiraishi, Manabu; Suzuki, Ken; Yamaguchi, Atsushi
Abstract: Excess deposition of extracellular matrix in the myocardium is a predictor of reduced left ventricular function. Although reducing the hemodynamic load is known to improve myocardial fibrosis, the mechanisms underlying the reversal of the fibrosis have not been elucidated. We focused on the elasticity of myocardial tissue, which is assumed to influence the fibroblast phenotype. Normal and fibrotic myocardium were cultured in 16 kPa and 64 kPa silicone gel‐coated dishes supplemented with recombinant TGFβ protein, respectively. Matrix‐degrading myocardium was cultured in 64 kPa silicone gel‐coated dishes with recombinant TGFβ protein and then in 16 kPa silicone gel‐coated dishes. Cardiac fibroblasts were cultured in this three‐part in vitro pathological models and compared. Fibroblasts differentiated into activated or matrix‐degrading types in response to the pericellular environment. Comprehensive gene expression analysis of fibroblasts in each in vitro condition showed Selenbp1 to be one of the genes responsible for regulating differentiation of fibroblasts. In vitro knockdown of Selenbp1 enhanced fibroblast activation and inhibited conversion to the matrix‐degrading form. In vivo knockdown of Selenbp1 resulted in structural changes in the left ventricle associated with progressive tissue fibrosis and left ventricular diastolic failure. Selenbp1 is involved in regulating fibroblast differentiation and appears to be one of the major molecules regulating collagen turnover in cardiac fibrosis. Abstract : Cardiac fibroblasts are transformed by hemodynamic loading into myofibroblasts that promote the production of ECM proteins. Cardiac fibrosis leads to the progression to heart failure. When the hemodynamic load is reduced, fibroblasts differentiate into matrix‐degrading fibroblasts and myocardial fibrosis improves. Selenbp1 is closely involved in the regulation of fibroblast phenotype and is one of the molecules that play an important role in collagen turnover in cardiac fibrosis.